Students' mathematical communication skill in co-op co-op type of cooperative learning model reviewed by productive disposition - Utami, Ika Wahyu Putri; Veronica, Rahayu Budhiati (Unnes Journal of Mathematics Education, 2021)
The purpose of this study are examine the effectiveness of co-op co-op type of cooperative learning model on the mathematical communication skill of 8th grade students, determine the effect of productive disposition on students' mathematical communication skill in co-op co-op type of cooperative learning model, and describe students' mathematical communication skill reviewed by productive disposition in co-op co-op type of cooperative learning model. The research method used is mixed method. The results showed that: 1) the mathematical communication skill of 8th grade students in co-op co-op type of cooperative learning model achieved classical completeness criteria, 2) the average of mathematical communication skill of 8th grade students in the co-op co-op type of cooperative learning model achieved minimum completeness criteria, 3) there is an effect of productive disposition on mathematical communication skill in the co-op type of cooperative learning model, 4) subjects with high productive disposition are able to achieve one indicator well and five indicators are achieved imperfectly. Subjects with medium productive disposition are able to achieve all indicators of mathematical communication skill imperfectly. Subjects with low productive disposition are able to achieve four indicators of mathematical communication skill imperfectly.